Implementation of Appropriate Site Development, Material Recycle, Indoor Health and Comfort in Shopping Buildings - Baringin, David Kiki (Universitas Buddhi Dharma/Fakultas Bisnis/Program Studi Akuntansi, 2021)
This study aims to examine the implementation of Appropriate Site Development, Material Recycle, Indoor Health and Comfort and its effect on the operational costs of property management. This study used primary data obtained from questionnaires sent to the property managers. The data were then processed by using the content analysis and were validated by interviews with informants. The results of the research showed that the managers of malls in Indonesia agree to implement green building standards due to cost and benefit considerations. This proves that the Property Managers should not only pay attention to profits but must pay attention to the environmental aspects (planet) and the people around the company. Therefore, a property management company should begin to implement sustainable building management. This study contributes to practical implications for property management to manage the building based on green building standards and building renovation into green building or retrofit.